Active women over 50: study protocol for RCT of a low-dose information and support program to promote physical activity behaviour change - Geraldine Wallbank; Catherine Sherrington; Colleen G. Canning; Leanne Hassett; Roberta Shepherd; Bethan Richards; Catherine Mackay; Anne Tiedemann (BMC, 2019)
Abstract Background There is compelling evidence that physical activity has many physical and mental health benefits and can delay the development of disability in older age. However, uptake of this health behaviour is sub-optimal in working women in their middle age. This trial aims to establish the impact of a low-dose information program, incorporating follow-up support using behaviour change techniques, compared with a wait-list control group, on physical activity among women aged 50+ years. Methods 100 female university or health service employees aged 50 years and over who are not sufficiently active according to national guidelines will be recruited and randomised to: [1] attend one information session at the worksite with follow-up email support and provision of resources including use of an activity tracker (Fitbit) for 3 months and free trial class at the university sports facility, or [2] a wait-list control to receive the intervention after the 3-month follow-up period. The primary outcome will be the proportion of people achieving 10,000 steps/day at 3 months post randomisation. Secondary outcomes will include the proportion of people achieving national guideline-recommended physical activity levels, the average self-reported hours of physical activity per week, perceived benefits of and barriers to exercise participation, physical functioning, and mood. Analyses will be planned, conducted while masked to group allocation and will use an intention-to-treat approach. Discussion This randomised controlled trial will evaluate the impact of a simple intervention using behaviour change techniques to increase physical activity participation in insufficiently active working women over the age of 50. Trial registration ACTRN12617000485336, prospectively registered, approved 04/04/2017.